Randomized controlled trial of a theory-informed mHealth intervention to support ART adherence and viral suppression among women with HIV in Mombasa, Kenya: preliminary efficacy and participant-level feasibility and acceptability - Frances M. Aunon; George Wanje; Barbra A. Richardson; Linnet Masese; Thomas A. Odeny; John Kinuthia; Kishorchandra Mandaliya; Walter Jaoko; Jane M. Simoni; R. Scott McClelland (BMC, 2023)
Abstract Background Mobile Health ("mHealth") interventions have shown promise in improving HIV treatment outcomes for stigmatized populations. This paper presents the findings from a randomized controlled trial to assess the efficacy, participant-level feasibility and acceptability of a theory-informed mHealth intervention, Motivation Matters!, designed to improve viral suppression and ART adherence among HIV-seropositive women who engage in sex work in Mombasa, Kenya. Methods A total of 119 women were randomized between the intervention and standard of care control. The primary outcome examined viral suppression (≤ 30 copies/mL) six months following ART initiation. ART adherence was assessed monthly using a visual analogue scale. Participant-level feasibility was measured through response rates to study text messages. Acceptability was assessed through qualitative exit interviews. Results Six months following treatment initiation, 69% of intervention and 63% of control participants were virally suppressed (Risk Ratio [RR] = 1.09, 95% Confidence Interval [95% CI] (0.83, 1.44). Among women who were viremic at baseline and endorsed engagement in sex work, 74% of women in the intervention arm compared with 46% of women in the control arm achieved viral suppression at month six RR = 1.61, 95% CI (1.02, 2.55). Adherence was higher in intervention versus control participants every month. All participants responded to at least one message, and there was a 55% overall response rate to intervention text messages. Qualitative exit interviews suggested high acceptability and perceived impact of the intervention. Conclusion The improvements in ART adherence and viral suppression, combined with encouraging data on feasibility and acceptability, provides preliminary evidence that Motivation Matters! could support ART adherence and viral suppression in women who engage in sex work. Trial registration This trial was registered with ClinicalTrials.gov (NCT02627365, 10/12/2015; http://clinicaltrials.gov ).